Electrochemical impedance spectroscopy based estimation of the state of charge of lithium-ion batteries. (November 2016) - Westerhoff, U.; Kroker, T.; Kurbach, K.; Kurrat, M.
Highlights: The Study show how the state of charge can be estimated with impedance spectra and a simplified equivalent circuit. Impedance spectra of self-made film batteries (=50 mAh) were performed in a voltage range from 3.0 to 4.2 V. The results show that electrochemical impedance spectroscopy can be applied for the estimation of the state of charge. Abstract: The increasing market demand for electric vehicles requires a continuous development and improvement of battery systems. A crucial aspect is the application of analytical methods to characterize the battery systems in the most exact way. At the same time these methods should remain as simple as possible. The current analysis procedures use essentially the battery system- and battery cell-characteristic of the voltage curve in relaxation- and operation-time. These approaches alone are not conclusive enough due to the influences of relaxation time and varying load currents. In recent years, methods based on electrochemical impedance spectroscopy (EIS) have found application for accurate analysis of occurring electrochemical processes and diagnosis of lithium ion batteries. This publication aims to show how the state of charge can be predicted with the use of EIS and a simplified equivalent circuit for redundant supplementing the OCV-method (open circuit voltage) and the current- counting method. Therefore film batteries with a graphite anode and a Ni1/3 Mn1/3 Co1/3 cathode are charged and discharged according to a specified procedure. The battery is (dis)charged with steps of 10% followed by an EIS measurement. The measured data is used to determine the elements of the simplified equivalent circuit. These elements are analyzed for their different values at various states of charge. From these measurements can be concluded that EIS can be applied for the estimation of state of charge (in the middle range) as redundant method to other estimation methods. It therefore provides an additionally methods by which statements about the battery conditions can be made.